A new technique for ranking a large number of attributes - M. Jacobs; M. Hedley (South African Journal of Business Management, 1983)
In certain market research surveys, problems may be encountered when respondents are required to rank a large number of attributes. In this article, we propose a method of breaking down the attribute list into manageable groups, and present an algorithm for constructing an overall ranking. A step-by-step illustration of the algorithm is given. The performance of the algorithm in a practical situation is examined.In sekere marknavorsings duik probleme op wanneer respondente 'n groot getal kenmerke in rangorde moet plaas. In hierdie artikel, word 'n nuwe metode voorgestel wat die kenmerke in beheerbare groepe lys en opbreek, en 'n algoritme vir die daarstelling van 'n algehele rangorde word voorgestel. 'n Stap-vir-stap illustrasie van die algoritme word gegee en die prestasie daarvan word in 'n praktiese voorbeeld ondersoek.
Keywords: 650